Evaluation of a Novel Method of Teaching Endobronchial Ultrasound: Physician- Versus Respiratory Therapist-Proctored Simulation Training - David Ryan Stather; Alex Chee; Paul MacEachern; Elaine Dumoulin; Christopher A Hergott; Jacob Gelberg; Sandra D Scott; Sylvia De Guzman; Alain Tremblay (Canadian Respiratory Journal)
BACKGROUND: Computer endobronchial ultrasound (EBUS) simulators have been demonstrated to improve trainee procedural skills before attempting to perform EBUS procedures on patients.